THE EFFECTIVENESS OF ENVIRONMENTAL DISPUTE RESOLUTION THROUGH NON-LITIGATION IN THE TERRITORIAL WATERS AND JURISDICTIONAL WATERS OF THE REPUBLIC OF INDONESIA - Mahipal, Mahipal; Wahyudin, Muhammad Nur Hussein; Wahyudin, Muhammad Yuusuf; Arkham, Muhammad Nur; Riadi, Septa; Dewantara, Esza Cahya; Wahyudin, Yudi (Politeknik Kelautan dan Perikanan Dumai, 2025)
This study aims to examine the effectiveness of the law in resolving environmental disputes through non-litigation mechanism in the territorial waters and jurisdiction of the Republic of Indonesia. This study was conducted by analysing the process and results of handling environmental disputes handled through non-litigation mechanism by the Ministry of Environment (KLH), especially the Directorate of Environmental Dispute Resolution. This study uses a qualitative analysis method with a case study approach involving documentation and interviews with related parties at KLH. The focus of the study is to assess the success of the dispute resolution mechanism through non-litigation, the obstacles faced, and the contribution of legal policies in protecting the environment, especially in waters that have complexities related to the rights and obligations of the state and other actors. The results of this study are expected to provide recommendations for improving the environmental dispute resolution system through non-litigation mechanism in Indonesia, with the aim of increasing the effectiveness of environmental protection in the territorial waters and jurisdiction of Indonesia.